2012
DOI: 10.1007/s10257-012-0206-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of organizational culture for grounding, management, guidance and effectiveness of enterprise architecture principles

Abstract: Enterprise architecture management (EAM) has become a widely acknowledged approach for guiding the continuous change of increasingly complex organizations. While methods and models for describing and analyzing enterprise architectures (EA) have been extensively discussed, principles guiding an EA's design and evolution are hardly covered in existing research. The paper at hand therefore analyzes the mechanisms of EA principles (EAP), that is EAP grounding, EAP management, and EAP guidance and their effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 71 publications
(98 reference statements)
2
41
0
2
Order By: Relevance
“…Schniederjans and Yadav (2013) found that trust issues still persist between architects and business stakeholders, adversely affecting EAI outcomes. Researchers have sought to explain the "gap" in the architect and stakeholder relationship in terms of differences in the motivations and viewpoints of architects and stakeholders (Faller & De Kinderen, 2014), organizational incentives and rewards (Foorthuis et al, 2016), conflicting assumptions and expectations associated with EAI activities (Aier, 2014), and the inability of architects to coordinate EAI activities across different functional groups (Espinosa, Armour, & Boh, 2010). Sessions (2009) describes the gap between architects and their stakeholders in terms of sensemaking and argues that stakeholders may have difficulty engaging with the EAI and that architects must eliminate any barriers to stakeholder understanding: "sometimes there is an atmosphere of mystique around enterprise architecture that makes it unnecessarily complicated, resulting in lack of understanding by the people that need to understand it" (Sessions, 2009, p. 9).…”
Section: Enterprise Architecture Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…Schniederjans and Yadav (2013) found that trust issues still persist between architects and business stakeholders, adversely affecting EAI outcomes. Researchers have sought to explain the "gap" in the architect and stakeholder relationship in terms of differences in the motivations and viewpoints of architects and stakeholders (Faller & De Kinderen, 2014), organizational incentives and rewards (Foorthuis et al, 2016), conflicting assumptions and expectations associated with EAI activities (Aier, 2014), and the inability of architects to coordinate EAI activities across different functional groups (Espinosa, Armour, & Boh, 2010). Sessions (2009) describes the gap between architects and their stakeholders in terms of sensemaking and argues that stakeholders may have difficulty engaging with the EAI and that architects must eliminate any barriers to stakeholder understanding: "sometimes there is an atmosphere of mystique around enterprise architecture that makes it unnecessarily complicated, resulting in lack of understanding by the people that need to understand it" (Sessions, 2009, p. 9).…”
Section: Enterprise Architecture Implementationmentioning
confidence: 99%
“…Authors' prescriptions for improving relations with stakeholders are varied and include enhanced management training of architects (Donaldson et al, 2015), increased business exposure for architects (Ross et al, 2006), more vigorous and rigorous use of structured methods (Aier & Schelp, 2010), and a variety of mechanisms for facilitating closer interaction between architects and stakeholders, such as methods for understanding organizational culture and subcultures (Aier, 2014), governance processes (Mocker, Ross, & Hopkins, 2015), and interdisciplinary architecture teams and liaison positions (Aier, Riege, & Winter, 2008;Strano & Rehmani, 2007). Some researchers have proposed new methodologies specifically designed to facilitate more significant stakeholder involvement (Jahani, Reza Seyyed Javadein, & Abedi Jafari, 2010).…”
Section: Enterprise Architecture Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…The common goal shared by all its components is to provide the necessary and promised support for its customers. Therefore, having a contact center system design can be a valuable basis for the process guiding the evolution of an organization by providing adequate representation of the current and desired states of the enterprise …”
Section: Contact Centers From a Systems Perspectivementioning
confidence: 99%
“…Is it because of the skills and behaviors of the enterprise architects or is it because they have the ability to connect content with money? Although we are aware of the growing number of research on organizational culture and EA, more research is needed to get a better understanding of what determines successful involvement of EA in IT decision-making and what not [36], [37].…”
Section: ) Need For Better Understanding Of What Determines Successfmentioning
confidence: 99%